Analisis Rasio Keuangan dalam Menentukan Investasi Saham pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2018-2022 - Khasan, Muhammad; Purwanto, Setiyo (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This research aims to determine the effect of Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), and Earning Per Share (EPS) to stock price in banking companies listed on the Indonesia Stock Exchange (IDX) period 2018-2022. The independent variables (X) in this research are ROA (X1), ROE (X2), DER (X3), and EPS (X4). Meanwhile, the dependent variable (Y) in this research is stock price. The method used in this research is descriptive quantitative method. The population in this research is all banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period totaling 46 companies. The method for determining the research sample used purposive sampling, the total research sample was 27 companies and the number of observations was 135 companies. Based on the research results, it shows that partially ROA, ROE, and DER have no effect and are not significant on stock price, while EPS partially has a significant effect on stock prices. Simultaneously ROA, ROE, DER, and EPS have a significant effect on the stock prices.